Tren Penyesuaian Diri Pada Mahasiswa Di Indonesia - Nia Bening Mutiara; Citra Finky Lestary; Qarsela Tiara Umardi; Alrefi Alrefi (Journal of Society Counseling, 2023)
This research can help new students learn about self-adjustment, the various reasons why students find it difficult to adjust to the university environment, and what can help new students in adjusting. Because self-adjustment definitely occurs in new students who enter the world of college, this research can provide a good understanding of self-adjustment. Every new student going through the adjustment process will undoubtedly run across problems. Good self-concept individuals will readily transition to a new environment and require help from numerous sources, including parents and friends, who also aid in the adjustment process for new pupils. using techniques for literary analysis. Aspects are the main emphasis of the literature evaluation, which draws from studies published in national publications.